Netypická bolest při ruptuře děložní - Mikešová, M; Fait, T; Kratochvíl, B; Hájek, Z (Ceska gynekologie, 2012)
OBJECTIVE: To give attention to the rare complication of pregnancy. DESIGN: Case report. SETTINGS: Dept. of Obstetric and Gynecology, 1st Faculty of Medicine, Charles University and General Faculty Hospital Prague. METHODS: Description of acute abdominal pain which imitated the appendicitis in case of the uterine rupture. CONCLUSION: The uterine rupture is the rare and very dangerous complication of pregnancy. In the time of increasing number of the cesarean section and the operation on the uterine wall, we must thing on the uterine rupture.
Keywords: Female; Pregnancy Complications; Abdomen, Acute; Humans; dospělí; Appendicitis; apendicitida; komplikace těhotenství; těhotenství; lidé; odumření plodu; Diagnosis, Differential; diferenciální diagnóza; ženské pohlaví; Pregnancy; Adult; Uterine Rupture; Fetal Death; ruptura dělohy; akutní bolest břicha